Analisis Pendapatan Usahatani Jagung Di Desa Pinaesaan Kecamatan Tompasobaru Kabupaten Minahasa Selatan (Analysis of Income from Corn Farming in Pinaesaan Village, Tompasobaru District, South Minahasa Regency) - Sumual, Dandi Freike; Pangemanan, Lyndon Reindhart Jacob; Sondakh, Mex Frans Lodwyk (Journal of Agribusiness and Rural Development (Jurnal Agribisnis dan Pengembangan Pedesaan), 2023)
Farming is a science that studies how a farmer allocates existing resources effectively and efficiently to obtain high profits at a certain time. Judging from some of the meanings above, of course the science of farming is very important in agricultural science. This study aims to analyze the results of corn farming income in Pinaesaan Village, Tompaso Baru District, South Minahasa Regency. The research was conducted from March to May 2023. The data collection method used observation techniques. Respondents in this study consisted of 21 people selected using the techniquepurposive sampling. The results showed that the fixed costs incurred were Rp. 261,456, - and a variable cost of Rp. 4,959,558, - and the average total costs incurred by farmers corn is Rp. 5,055,471/Ha. The production of corn is 1,685 kg with a selling price of Rp. 5,000.- per kilogram generates revenue of Rp. 8,425,000/Ha so that it can generate an average income of Rp. 3,369,529/Ha.